Statement by The Managing Director on the Work Program of The Executive Board : June 11, 2020. (Policy Papers; Policy Paper, 2020)
The COVID 19 crisis continues to take a heavy human and economic toll. The outlook remains highly uncertain as many countries are facing the economic fallout of the pandemic. This has led to an unprecedented surge in demand for Fund support and a strain on staff resources. Against this backdrop, and in line with the strategic priorities laid out in the Spring 2020 Global Policy Agenda and the International Monetary and Financial Committee Communique, this crisis focused Work Program (WP) lays out essential work during May to October aimed at helping countries to mitigate the crisis, restore stability, and prepare for a strong and sustainable recovery. The WP implies a large increase in Board items compared with last year, reflecting mostly informal and more frequent updates on how this rapidly evolving crisis affects economic and financial developments and relevant policies. Other work streams are delayed; they are outlined in the WP and will be included in the Board agenda once there is more clarity on how the evolution of the pandemic will impact crisis related work.